Pedotransfer function to predict density of forest soils in Switzerland. Issue 3 (5th April 2016) - Nussbaum, Madlene; Papritz, Andreas; Zimmermann, Stephan; Walthert, Lorenz
Abstract: Soil density is an important soil property, but respective measurements are usually scarce. With data from 559 mineral soil horizons (134 sites) we developed a linear regression pedotransfer function (PTF) for the density of forest soils (sieved to ≤ 2 mm). The field estimate of density was the most important covariate. RMSE of 0.205 Mg m −3 and R 2 of 0.67, calculated on independent data (131 horizons), were better than the statistics obtained by published, recalibrated PTF (RMSE 0.271–0.324 Mg m −3 ; R 2 0.28–0.42).